Osteoimmunology: Influence of the Immune System on Bone Regeneration and Consumption - Limmer, Andreas; Wirtz, Dieter C. (Zeitschrift für Orthopädie und Unfallchirurgie, 2017)
Background Stimulating bone regeneration is a central aim in orthopaedic and trauma surgery. Although the replacement of bone with artificial materials like cement or apatite helps to keep up bone stability, new bone often cannot be regenerated. Increasing research efforts have led to the clinical application of growth factors stimulating bone growth (e.g. bone morphogenic protein, BMP) and inhibitors preventing bone consumption (e.g. RANKL blocking antibodies). These factors mostly concentrate on stimulating osteoblast or preventing osteoclast activity.Current Situation It is widely accepted that osteoblasts and osteoclasts are central players in bone regeneration. This concept assumes that osteoblasts are responsible for bone growth while osteoclasts cause bone consumption by secreting matrix-degrading enzymes such as cathepsin K and matrix metalloproteinases (MMP). However, according to new research results, bone growth or consumption are not regulated by single cell types. It is rather the interaction of various cell types that regulates bone metabolism. While factors secreted by osteoblasts are essential for osteoclast differentiation and activation, factors secreted by activated osteoclasts are essential for osteoblast activity. In addition, recent research results imply that the influence of the immune system on bone metabolism has long been neglected. Factors secreted by macrophages or T cells strongly influence bone growth or degradation, depending on the bone microenvironment. Infections, sterile inflammation or tumour metastases not only affect bone cells directly, but also influence immune cells such as T cells indirectly. Furthermore, immune cells and bone are mechanistically regulated by similar factors such as cytokines, chemokines and transcription factors, suggesting that the definition of bone and immune cells has to be thought over.Outlook Bone and the immune system are regulated by similar mechanisms. These newly identified similarities between bone and the immune system imply that medication developed for tumour and autoimmune patients could also be applied in bone diseases.Hintergrund Die gezielte Regeneration von Knochenschäden ist ein zentrales Ziel der Orthopädie und Unfallchirurgie. Die Verwendung von Knochenersatzmaterialien (z. B. Knochenzement), welche die Struktur und Stabilität des Knochens wiederherstellen sollen, reicht nicht aus, um langfristig funktionsfähigen Knochen wiederherzustellen. Als Folge einer voranschreitenden Forschung werden derzeit Wachstumsfaktoren zur Steigerung des Knochenwachstums und Inhibitoren zur Verminderung des Knochenabbaus eingesetzt.Stand der Forschung Osteoblasten und Osteoklasten sind zentrale Bausteine des Knochenmetabolismus. Während Osteoblasten für den Knochenaufbau verantwortlich gemacht werden, wird eine deregulierte Osteoklastenaktivität als Ursache für massiven Knochenabbau im Zuge der Osteoporose oder nach Knochenmetastasierung angesehen. Aktuelle Forschungsergebnisse der letzten Jahre zeigen jedoch, dass die Knochenbildung komplexer ist. So benötigen Osteoblasten für die Differenzierung und Vermehrung Faktoren aktivierter Osteoklasten, während die Osteoklastenaktivität von Osteoblasten abhängt. Kürzlich wurde außerdem der enorme Einfluss des Immunsystems auf das Knochenwachstum erkannt. Welchen Einfluss Immunfaktoren auf den Knochenmetabolismus haben, hängt stark von dem Milieu ab, das im Knochen vorherrscht. Während „im Normalfall“ Zytokine der TGF-β-Familie (neben TGF-β eine Reihe von „bone morphogenic proteins“, BMPs) den Knochenaufbau stimulieren, induzieren Entzündungen infolge von Infektionen oder Zellschäden den Knochenabbau 4, 5, 11.Ausblick Ein besseres Verständnis der Vorgänge, die das Knochenwachstum regulieren, und insbesondere die Rolle des Immunsystems wird zur Entwicklung von neuen Medikamenten zur Stimulation des Knochenaufbaus beitragen. Aufgrund der starken Überlappung von Wirkmechanismen des Knochenmetabolismus und von Immunfunktionen könnten Medikamente, die gegen Tumoren und Autoimmunerkrankungen entwickelt wurden, in der Knochenregeneration Verwendung finden.
Keywords: osteoimmunology; osteoblast; osteoclast; bone regeneration